Trening kompetencji międzykulturowej na podstawie analizy podręcznika do nauki języka szwedzkiego dla uczniów na poziomie średniozaawansowanym Rivstart B1+ B2 - Iwaniak, Kamil (Scripta Neophilologica Posnaniensia, 2021)
The aim of the article is to reflect upon the conveying of cultural content in the foreign language classroom that contributes to the development of intercultural competence. It has been attempted to systematize the multitude of aspects which characterizes the use of cultural studies in language classes. It has been done by drawing attention to reasons for taking into consideration this sort of knowledge while preparing the lessons and teaching methods that are in favour of an insightful contact with a cultural content. Attention has been primarily drawn to the coursebook Rivstart B1 +B2 that is intended for intermediate students of Swedish language. The coursebook has been subjected to a comprehensive analysis with regard to the cultural learning.